Dephosphorylation of the Atg1 kinase complex by type 2C protein phosphatases. (4th May 2019) - Memisoglu, Gonen; Haber, James E.
ABSTRACT: In budding yeast, Atg1 kinase, together with Atg13 and Atg17, forms a complex that is essential for autophagy. Previous work showed that the Atg1 kinase complex is regulated extensively by phosphorylations. Our recent paper demonstrates that type 2C protein phosphatases Ptc2 and Ptc3 are involved in the dephosphorylation of Atg13 and Atg1 kinase to promote autophagy.